Pengukuran Kinerja PT Nitto Alam Indonesia (NAI) Menggunakan Metode Balanced Scorecard - Rifanisa Azzahra; Budi Sulistyo; Nanang Suryana (IAI Nasional Laa Roiba Bogor, 2024)
A company engaged in manufacturing to produce bolts and screws located in Tangerang Regency, Banten called PT Nitto Alam Indonesia. The company still depends on the number of product sales in measuring its performance. There is a fluctuating level of sales from year to year. However, there are problems in the product sales process caused by the pandemic in 2020, resulting in a decrease in product sales compared to previous years. In order to improve the quality of competitiveness in terms of financial and non-financial aspects, it is necessary to design a company performance measurement tool that takes into account the company's internal and external factors. This allows for the development of a Key Performance Indicator (KPI) using the Balaced Scorecard (BSC) method. Through interviews and questionnaires with management, a SWOT evaluation was conducted. Evaluation in terms of strengths, weaknesses, opportunities, and threats that exist in the company is used to determine strategies and strategic goals using four balanced scorecard perspectives. The goal is to realize the company's vision and mission from the measurement of key performance indicators. Furthermore, using the Analytical Hierarchy Process (AHP), a comparison is made to determine which components have the highest priority level.